Kappa van E.W.J Verwey behorende bij zijn eredoctoraat in de Technische Wetenschappen verleend door de TH Delft
Kappa van E.W.J Verwey behorende bij zijn eredoctoraat in de Technische Wetenschappen verleend door de TH Delft.